A scientometric study of betel quid chewing and oral cancer and precancerous lesions with distinct regional characteristic - Gengru Wang; Zhonglin Yu; Tong Ji; Linjun Shi; Wei Liu (Elsevier, 2023)
Scientometric analysis is a useful tool that utilizes bibliometric data to measure scientific output of a disease or region in a particular field. In this report, we comprehensively provide bibliometric characteristics of all the papers on betel quid (BQ)-related cancer and precancerous lesions. There are 1403 papers on BQ-related cancer and precancerous lesions published until 2022 in the Scopus database. China (mainland and Taiwan region), India, United States, and United Kingdom contribute 1214 (86.5%) papers and 34,120 (91.9%) citations of all the papers. The number (457), citations (14,573), and h index (60) of the papers originated from Taiwan region stably remain in the first. The most frequent research keyword is arecoline, followed by drug, prevalence, metabolism, carcinogenesis, and pathology. Areca nut and BQ cessation program by Taiwan government has demonstrated a significant positive impact on oral cancer prevention. Collectively, the scientific output of BQ-related cancer and precancerous field represents distinct regional characteristic. BQ-related cancer prevention is still a long way off. Encouragingly, Taiwan region is well ahead in this way.